2014
DOI: 10.1111/ane.12336
|View full text |Cite
|
Sign up to set email alerts
|

Super-refractory status epilepticus in West China

Abstract: This study was the first to use the statistical percentage of SRSE. Approximately 12.2% of SE cases will result in SRSE, which is a challenging medical situation for doctors. Patients with first episodes and acute encephalitis were also prone to develop SRSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 22 publications
7
25
2
2
Order By: Relevance
“…The concept of SRSE was introduced a few years ago and requires an SE that continues or recurs ≥24 h after the onset of anesthetic therapy and includes those cases in which SE recurs on the reduction or withdrawal of anesthesia. Although the transition from nonrefractory to refractory SE may be minor, and merely indicates that a patient needs one additional intravenous AED to stop SE, the SRSE is, by definition, always characterized by the failure of initial anesthetic therapy to stop SE and by a duration of ventilation of >24 h. SRSE occurs in approximately 12–26% and RSE in 14–57% of all cases of SE . Our results of a relative prevalence of SRSE of 9.7% and of RSE of 50.1% are in line with the results of these studies.…”
Section: Discussionsupporting
confidence: 90%
“…The concept of SRSE was introduced a few years ago and requires an SE that continues or recurs ≥24 h after the onset of anesthetic therapy and includes those cases in which SE recurs on the reduction or withdrawal of anesthesia. Although the transition from nonrefractory to refractory SE may be minor, and merely indicates that a patient needs one additional intravenous AED to stop SE, the SRSE is, by definition, always characterized by the failure of initial anesthetic therapy to stop SE and by a duration of ventilation of >24 h. SRSE occurs in approximately 12–26% and RSE in 14–57% of all cases of SE . Our results of a relative prevalence of SRSE of 9.7% and of RSE of 50.1% are in line with the results of these studies.…”
Section: Discussionsupporting
confidence: 90%
“…The 3-month mortality rates for non-RSE, RSE, and SRSE were 18.2, 20.0, and 45.5% respectively. The mortality rates of RSE and SRSE in our study are a little higher than results from one German study [14] but were consistent with the results of one study from West China [15]. Forty-two patients were lost in the follow-up for evaluating DRE development (17 cases lost until September 2012, another 25 cases lost until November 2017), 1 patient was excluded due to lack of treatment compliance.…”
Section: Study Population and Outcomessupporting
confidence: 89%
“…Hay et al [6] performed a retrospective study of patients admitted to an intensive care unit with the primary admission diagnosis of SE in ­Australia and New Zealand, and they found that mortality decreased greatly from 2.6% in 2000 to 0.75% in 2013. The relevant studies in China revealed mortality rates of 16% in Hong Kong [7] and 7.1% in west China [12]. In the current study, we found that the mortality of SE in northeast China was 6.73%.…”
Section: Discussionsupporting
confidence: 51%
“…Whether age contributes to the progression of RSE/SRSE is still controversial. Some scholars proposed age as a high risk factor of RSE [19, 20], while others did not find an association between age and occurrence of RSE [12]. In our study, we noted a significant difference in the average age of the 2 groups, strongly suggesting that age is an independent risk factor for RSE.…”
Section: Discussioncontrasting
confidence: 45%